Penghijauan Perkarangan Rumah Warga Melalui Pembagian Bibit Cabai Dan Terong Di RT01 Sawah Lebar - Pratama, Abe Ariel; Saputra, Adi; Tanjung, Abimayu Prasetiyo; Ferdinan, Anand Junicas; Efendi, Asepri; Asyahri, Ahmad; Kharil, Khairil; Susena, Karona Cahya (LPPM Universitas Dehasen Bengkulu, 2026)
The limited utilization of residential yards has become a challenge for households in achieving environmental greening and food security. Many families leave their yards unused, resulting in lost opportunities for ecological and economic benefits. This community service program was designed to address the issue by encouraging residents to cultivate productive plants in their yards. The intervention involved distributing chili and eggplant seedlings, providing training on planting techniques, and conducting continuous monitoring of plant growth. Implementation steps included initial surveys of yard conditions, coordination with neighborhood leaders to determine seed requirements, seed distribution to households, training sessions on cultivation and maintenance, and follow-up observations to evaluate progress. The outcomes showed that residents began to use vacant land more effectively, creating greener and healthier surroundings. In addition, households gained supplementary food sources from their own harvests, contributing to family food security. This program demonstrates that simple interventions such as seed distribution and mentoring can foster sustainable environmental practices, strengthen community resilience, and support the achievement of Sustainable Development Goals (SDGs), particularly Goal 2 (Zero Hunger) and Goal 11 (Sustainable Cities and Communities).